Comprehensive Demonstration of Greater Significance of Infaq fi Sabilillah - Rashid, Md. Mamunur (Journal of Quranic Sciences and Research, 2025)
“Infaq fi Sabilillah: spending in the way of Allah (SWT)," other than Zakat, is usually considered a voluntary act of good deed in Islam. Also, there is a common understanding among Muslims that this spending is just an optional act of worship and is less important in terms of significance and status than mandatory acts of worship. However, the statements of Allah (SWT), the sayings of the Prophet (PBUH), and the opinions of scholars highlight the high importance of “spending in the way of Allah (SWT).” This research aims to demonstrate the greater significance of “Infaq fi Sabilillah” as an act of good deed in Islam. Many Qur’anic verses and Hadiths of the Prophet (PBUH) assert the great importance and status of spending in the way of Allah (SWT), even above those of some mandatory acts of worship. Also, according to the opinions of some scholars, there are occasions when spending, in addition to Zakat, becomes obligatory and necessary. The rewards of this spending and the consequence of not spending in the way of Allah (SWT) are also stated in some Qur’anic verses. Allah (SWT) has referred a believer in Al-Qur’an by various distinct qualities & names having some specific attributes. The activities of “Infaq fi Sabilillah” are the most mentioned attribute of a believer mentioned in those distinct qualities & names. Some relevant Qur’anic verses, the Hadiths of the Prophet (PBUH), and the opinions of scholars have been identified and presented in this paper. This paper demonstrates that “Infaq fi Sabilillah” is an act of greater significance in Islam.